The workshop as a technique to promote systemic environmental visions (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Within the framework of the University Extension Program Praxis of Food Sovereignty (UNLPam), various workshops on environmental awareness were conducted. In September 2022, on the occasion of the XVI Latin American Meeting of Students in Natural Resources and Environment (Santa Rosa, La Pampa), the workshop "Controversies about the perimeter fencing of the Provincial Reserve Parque Luro" was put into practice. It was a participatory and reflective critical meeting that not only allowed us to think about the pros and cons of the fence in the use of the Reserve, but also served to cast doubt on the first certainties about this management technique. Due to its modality, the workshop achieved moments and spaces of learning from the perspective of the “other”.
Keywords: participatory techniques; Provincial Reserve Parque Luro; management of natural reserves